Estudio de factibilidad para la implementación de una academia de música en la ciudad de Loja, provincia de Loja - Castro Celi, Carlos Andrés (2015)
The research entitled "Feasibility study for the implementation of a music academy in the city of Loja province of Loja" main objective was to determine the feasibility of a music academy specializing in guitar, piano and drums based on studies market, technical, financial and financial evaluation. This project aims to provide families of the city of Loja, a place where you can learn music in a pleasant and calm manner, starting with basic knowledge to enable them to develop these talents in music not only a sector but in all parts the world can take this knowledge. For this method as deductive and inductive used; technical survey and interviews that allowed them to gather relevant information for this project. For market research: market characteristics such as were identified: supply and demand, a statistical sampling was used whose size and sample selection was enough to get reliable results, giving a total score of 397 surveys distributed to different sectors Urban city of Loja having obtained the 189060 population census of 2010, this value 4 divided by the number of members of each family, giving a total of 42570 and the projected value for 2014 gives a value of 47265 families in urban parishes in the city of Loja. The market study: indicated that 81.61% of the population said they themselves would use our service, which the implementation of the music academy "LION MUSIC CIA LTDA" specializing in guitar, piano and drums would feasible City Loja 6 In the technical study: the size and location of the company was determined to be located in the same city of Loja, Parish Valley in Nueva Loja Av between Guayaquil and Salinas streets diagonally to the Plaza del Valle, place. It provides the conditions for its development, having all basic services. Installed capacity: In "LION MUSIC CIA LTDA" is 21600 services for a year, representing 4.58% of the unmet demand; while for capacity utilization it was estimated prudent to initiate the first year to 67% with an increase of 7% annually. As for the organizational study, this allowed to define the legal aspect of the business with the creation of functional, structural organizational positional and manual functions for each official, for proper process control service. In the financial study: the financial return of the project is determined from the first year in office, also could determine the costs in the same period and thus determine the net profit of the company. To carry out this project total investment of $ 8566.31 is counting had its own financing of 30% equivalent to $ 2,566.31 an external 70% amounting to $ 6,000 financed by the Banco de Loja in their line of production loans with an interest rate of 11.83% per month, within a period of three years. The financial assessment: Reflected positive financial indicators, with a projected five years a net present value of $ 4,449.21 and an Internal Rate of Return of 21.16% was obtained giving a cost benefit ratio of 15.54 CTV. for every dollar invested, the investment will pay off in 2 years, 11 months, 26 days. 7 Finally he came to establish findings and recommendations, the NPV and IRR are positive, with a profit of 10% for investors of this project is advisable to invest and start it. Finally, conclusions and recommendations which was reached with the research shows, the literature that served as a theoretical reference for the completion of the project and appendices and index.